2020
DOI: 10.1177/1943387520962691
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Aided Fracture Size Measurement in Orbital Fractures—An Alternative to Manual Evaluation

Abstract: Objective: We aimed to present a novel semiautomated tool for orbital fracture size measurement and to compare the variability of the proposed method with traditional manual measurements. Methods: Maximal anteroposterior (AP) and mediolateral (ML) dimensions of orbital fractures from computed tomography images were measured for 15 patients with unilateral orbital fractures by 2 surgeons manually and with a semiautomatic software. Variability was assessed with Bland-Altman limits of agreement plots and intra-cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…The results of our CT study showed that the height and the width of the left orbit and the height of the right orbit were significantly higher in Roma examinees, whereas the width of the right orbit was not statistically different between the ethnicities. The obtained results for these parameters were similar to the findings of previous CT studies conducted in Turkish and Indian populations [3,9,22]. The sex differences in anatomy of the orbital cavity were confirmed by various studies, with male orbits being significantly larger than female [9,11,16,23].…”
Section: Discussionsupporting
confidence: 88%
“…The results of our CT study showed that the height and the width of the left orbit and the height of the right orbit were significantly higher in Roma examinees, whereas the width of the right orbit was not statistically different between the ethnicities. The obtained results for these parameters were similar to the findings of previous CT studies conducted in Turkish and Indian populations [3,9,22]. The sex differences in anatomy of the orbital cavity were confirmed by various studies, with male orbits being significantly larger than female [9,11,16,23].…”
Section: Discussionsupporting
confidence: 88%
“…The studies included in this review reported varying levels of interobserver and intraobserver variability, with automatic methods generally demonstrating lower variability compared with manual and semiautomatic methods. For example, Saloniemi et al 6 (2021) compared interobserver and intraobserver variability among manual and computer-aided measurements in orbital fractures and found that the computer-aided method had lower variability. This finding suggests that automatic methods provide more consistent results and reduce discrepancies among observers.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the review of the current literature, automatic methods, such as computer-aided measurements and CT-based volumetric analysis, seem to provide the highest accuracy and reliability for measuring blowout fracture areas. These methods can reduce the influence of human error and improve consistency among different observers 6,30–33 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method has been used for orbital volume calculations. [10][11][12][13] Third, the resulting 3D models were saved in the cloud, and every individual anatomical structure was simplified to account for the processing power of current AR-HMDs, maintain optimal performance, and preserve all relevant anatomical details. Furthermore, visualization properties, such as color and transparency, were automatically optimized.…”
Section: Automatic Segmentation and Ar Workflowmentioning
confidence: 99%